CHROMIUM PICOLINATE PREVENTS OXIDATIVE DAMAGE TO CARDIOMYOCYTES UNDER CONDITIONS OF METABOLIC SYNDROME MODELING - Akimov, O.Y.; Mykytenko, A.O.; Mischenko, A.V.; Kostenko, V.O. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Introduction. Metabolic syndrome is a systemic pathology commonly associated with eating disorders that lead to excess calorie consumption. In addition to the development of obesity, metabolic syndrome is often associated with the development of myocardial damage. One of the universal mechanisms of cell damage is oxidative stress. The search for proper medication that will prevent oxidative damage to the myocardium and influence the pathogenetic links in the development of metabolic syndrome is a relevant area of research. Chromium picolinate is a promising agent for preventing myocardial damage in metabolic syndrome, as it may enhance lipolysis in adipocytes. Objectives. The aim of this work is to determine the effect of chromium picolinate on the production of superoxide anion radical, the activity of antioxidant enzymes, and the content of malondialdehyde in the heart of rats under conditions of experimental metabolic syndrome. Materials and methods. The study was performed on 24 Wistar rats weighing 200–260 g. The animals were assigned to four groups (n = 6 per group): control group; metabolic syndrome model group, in which metabolic syndrome(MS) was induced by administering a 20% fructose solution as the sole source of drinking water to the standard vivarium diet for 60 days; chromium picolinate group, which received chromium picolinate orally at a dose of 80 μg/kg daily for 60 days; combined group, receiving both chromium picolinate and the MS-inducing fructose regimen. Cardiac oxidative stress parameters were assessed in 10% heart homogenates. The following indicators were measured: basal and induced production of the superoxide anion radical, activity of superoxide dismutase (SOD) and catalase (CAT), and malondialdehyde (MDA) content. Results. Administration of chromium picolinate to animals modeled with metabolic syndrome reduces basal superoxide anion radical production in the heart of rats by 52.33% compared to the metabolic syndrome group. Under these conditions, NADPH-induced superoxide anion radical production and NADHinduced superoxide anion radical production are reduced by 20.13% and 20.69%, respectively, compared with the metabolic syndrome group. The activity of superoxide dismutase and catalase in the heart of rats under these conditions increases by 78.88% and 137.93%, respectively, compared to the metabolic syndrome group. The content of malondialdehyde in the heart of rats under the conditions decreases by 25.59% compared to the metabolic syndrome group. The content of OMP under these conditions does not change statistically significantly. The use of chromium picolinate effectively reduces the production of reactive oxygen species, enhances antioxidant defense, and reduces the intensity of lipid peroxidation in the heart of rats with metabolic syndrome. This work is a part of the initiative research project No. 0124U000092 “Highand low-intensity phenotypes of systemic inflammatory response: molecular mechanisms and new medical technologies for their prevention and correction”.